Benzoyl peroxide in the treatment of acne: are there potential health concerns? - Czyz, Sonia; Yang, Kerry; Jafarian, Fatemeh (Frontiers in Pediatrics, 2025)
Benzoyl peroxide is a widely used and effective topical treatment for acne vulgaris, particularly in pediatric and adolescent populations. Despite its established safety profile, recent concerns emerged regarding its potential to decompose into benzene, a known carcinogen, under specific environmental conditions, like elevated temperatures and exposure to ultraviolet radiation. In this paper we review the management of acne vulgaris in pediatric patients, examine the evidence supporting benzoyl peroxide use and explore the recent studies evaluating the association between benzoyl peroxide use and malignancy risk. While initial reports raised alarm over benzene formation, subsequent investigations have not demonstrated an increased risk of hematologic malignancies. Here, we assess the strengths and limitations of existing evidence and identify future research priorities. Additionally, we provide recommendations for the safe and evidence-based use of benzoyl peroxide in pediatric acne treatment.